2016
DOI: 10.1108/ccij-01-2015-0003
|View full text |Cite
|
Sign up to set email alerts
|

Exploring academic reputation – is it a multidimensional construct?

Abstract: Purpose -The purpose of this paper is to explore the possible congruence of an academic organization's reputation among various stakeholder groups. A potential measure of reputation that can be applied across multiple stakeholder groups gives an opportunity to compare their perceptions and therefore work toward a consistent reputation. The authors also tested the model of academic reputation as a multidimensional concept. Design/methodology/approach -The qualitative stage included 25 in-depth interviews with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 45 publications
0
47
0
1
Order By: Relevance
“…In other words, every survey participant answered 72 questions as the variables. The main reasons these criteria were selected are because it can serve as a repetition of the quality of the past activities of the university [80][81][82]. Also, these deduced criteria capture the reflected image the university creates of the students.…”
Section: Measurement and Weighting Criteriamentioning
confidence: 99%
“…In other words, every survey participant answered 72 questions as the variables. The main reasons these criteria were selected are because it can serve as a repetition of the quality of the past activities of the university [80][81][82]. Also, these deduced criteria capture the reflected image the university creates of the students.…”
Section: Measurement and Weighting Criteriamentioning
confidence: 99%
“…As previously mentioned, the term reputation was commonly used without a clear explanation, operationalization or a unique definition. One of the reasons for this lack of universal definition was the number of scientific disciplines that focus on reputation, such as strategic management, economics, marketing, market research, sociology, psychology and public relation (Verčič et al, 2016).…”
Section: University Reputation (Rep)mentioning
confidence: 99%
“…the universal appeal that an organization had for its key constituents in comparison with others (Fombrun and Van Riel, 1997). A later extension of this definition added that reputation was an estimate of the way an organization is experienced both, internally, among employees and externally, among other stakeholder groups, within its competitive and institutional surroundings (Verčič et al, 2016) Vidaver-Cohen(2007) suggested a conceptual framework for studying business school reputation. The proposed concept draws from the Reputation Institute and as major predictors of corporate reputation offers organizational performance, quality of products and services, leadership characteristics, management procedures, corporate social responsibility procedures, workplace climate and approach to innovations.…”
Section: University Reputation (Rep)mentioning
confidence: 99%
See 1 more Smart Citation
“…Rankings quickly attracted the attention of universities and politicians as they challenged opinions on reputation and excellence [19]. Verčič et al [20] explored academic reputation and compared their perceptions and work towards consistent reputation with 25 in-depth interviews with members of key stakeholder's groups. The high competition among universities for attracting students, public resources, social demand for transparency and competence use of funds has resulted in a growing interest in evaluating their performance through rankings.…”
Section: University Reputation (Ur)mentioning
confidence: 99%